How university students estimate effects of self-regulated learning experienced in upper secondary school - Kyburz-Graber, Regula; Notter, Philipp (Swiss Journal of Educational Research, 2019)
Self-regulated learning is increasingly promoted in upper secondary schools. A specific form is the “self-learning semester” (SLS) in an A-level upper secondary school, 11th grade. In this paper it is investigated how university students estimate their experiences with SLS and if any effects on their general learning competences can be shown. Students at the two universities in Zurich with SLS-experience were invited to answer to an online questionnaire. The questions were taken from previous studies and added by questions on SLS. Data from previous studies were used as comparison sample. Results show that students attributing benefit from SLS judge relevant general competences significantly higher than others. Outcomes are discussed in the light of coaching students in SRL-situations.